Potential Role of Natural Compounds as Anti-Angiogenic Agents in Cancer - Shanmugam, M.; Warrier, S.; Kumar, A.; Sethi, G.; Arfuso, Frank (2017)
BACKGROUND: Neovascularization, also known as angiogenesis, is the process of capillary sprouting from pre-existing blood vessels. This physiological process is a hallmark event in normal embryonic development as blood vessels generally supply both oxygen and nutrients to the cells of the body. Any disruption in this process can lead to the development of various chronic diseases, including cancer. In cancer, aberrant angiogenesis plays a prominent role in maintaining sustained tumor growth to malignant phenotypes and promoting metastasis. The leakiness in the tumor microvasculature is attributed to the tumor cells migrating to distal site organs and forming colonies. METHODS: In this article, we briefly review the various mediators involved in the angiogenic process and the anti-angiogenic potential of selected natural compounds against various malignancies. RESULTS: Several growth factors and their receptors such as vascular endothelial growth factor and receptor (VEGF/VEGFR), basic fibroblast growth factor and receptor (bFGF/FGFR), angiopoietins, and hypoxia inducible factors facilitate the development of angiogenesis and are attractive anti-cancer targets. Natural products represent a rich diversity of compounds for drug discovery and are currently being actively exploited to target tumor angiogenesis. CONCLUSION: Agents such as curcumin, artemisinin and its semi-synthetic derivatives, EGCG, pentacyclic triterpenoids, resveratrol, emodin, celastrol, thymoquinone and tocotrienols all have shown prominent anti-angiogenic effects in the preclinical models of tumor angiogenesis. Several semi-synthetic derivatives and novel nano-formulations of natural compounds have also exhibited excellent anti-angiogenic activity by increasing bioavailability and delivering the drugs to the sites of tumor angiogenesis.